Hypothermia and its role in patients with ST-segment-elevation myocardial infarction and cardiac arrest - Keller, Karsten; Sagoschen, Ingo; Schmitt, Volker H.; Münzel, Thomas; Gori, Tommaso; Hobohm, Lukas (Frontiers in Cardiovascular Medicine, 2022)
Background Patients suffering cardiac arrest resulting from ST-segment-elevation myocardial infarction (STEMI) are at very high risk of death. In addition to reperfusion strategies, therapeutic hypothermia is recommended for cardiac arrest patients who remain unconscious after resuscitation. However, data analysis of the impact of therapeutic hypothermia on survival showed inconsistent results. We aimed to investigate the benefits of therapeutic hypothermia in STEMI patients after cardiopulmonary resuscitation (CPR). Methods Patients with STEMI who received CPR were identified after nationwide German inpatient data (2005–2019) were screened. These patients were stratified for therapeutic hypothermia. The impact of hypothermia on mortality and adverse in-hospital outcomes was analyzed. Results Overall, 133,070 inpatients with STEMI and CPR (53.3% aged ≥70 years; 34% females) were recorded in Germany between 2005 and 2019, of which 12.3% (16,386 patients) underwent therapeutic hypothermia. Females (23.8 vs. 35.4%, p < 0.001) and patients aged ≥70 years (34.9 vs. 55.9%, p < 0.001) were less frequently treated with therapeutic hypothermia. The in-hospital case fatality rate was lower for STEMI with CPR and subsequent therapeutic hypothermia than for treatment without therapeutic hypothermia (53.5 vs. 66.7%, p < 0.001). Therapeutic hypothermia was independently associated with a reduced in-hospital case fatality rate OR 0.83 [95% confidence interval (CI) 0.80–0.86], p < 0.001. In addition, therapeutic hypothermia was associated with an increased risk for stroke (OR 1.37 [95% CI 1.25–1.49], p < 0.001), pneumonia (OR 1.75 [95% CI 1.68–1.82], p < 0.001), and acute kidney injury (OR 2.21 [95% CI 2.07–2.35], p < 0.001). Conclusion Therapeutic hypothermia is associated with a survival benefit for STEMI patients after cardiac arrest.